EFEKTIVITAS PELAYANAN PEMERINTAH TERHADAP MASYARAKAT DI KECAMATAN RIMBA MELINTANG KABUPATEN ROKAN HILIR TAHUN 2014-2015 - Suprison "; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this thesis is to find out the effectiveness of family card service, identity card/electronic identity card and birth, certificate at Rimba Melintang districk, and to find out the influencing factors of the effectiveness of family card service, identity card/ electronic identity card and birth certificate at Rimba Melintang district. Academic side hopes the public administration getting the benefit. In development side. This research used field research methodology giling description about the effectiveness of family card service, Electronic identity card and birth certificate at Rimba Melintang district of Rokan Hilir regency. The data collecting technigue used observation technigue, interview and guestionnaire by choosing informan which technically and functionally in giling service to the society. The data analysis technigue is gualitative and support by guantitative data.From this research describe that the service implementation expecially in society administration and civil registration done as the mechanism and the rule, by using some service indicators as simplicity. The Clarity and Certain ty for procedure and fee. The safety and comfortness intrastructure The ease of getting information and the role of service. The economy fee of family card service, Electronic identity card and birth certificate is in category of Rp.10.000 - Rp.15.000, the balance justice, the puctuality is in category of 1-2 days and the efficiency is in right category. The influencing factors are, 1) official resource, 2) infrastructure, 3) society awarness.Key Words : Effectiveness, Public Services